Advances in Intelligent Control Systems and Computer Science - Dumitrache, Loan (Advances in Intelligent Systems and Computing, 2013)
The conception of real-time control networks taking into account, as an integrating approach, both the specific aspects of information and knowledge processing and the dynamic and energetic particularities of physical processes and of communication networks is representing one of the newest scientific and technological challenges. The new paradigm of Cyber-Physical Systems (CPS) reflects this tendency and will certainly change the evolution of the technology, with major social and economic impact. This book presents significant results in the field of process control and advanced information and knowledge processing, with applications in the fields of robotics, biotechnology, environment, energy, transportation, et al.. It introduces intelligent control concepts and strategies as well as real-time implementation aspects for complex control approaches. One of the sections is dedicated to the complex problem of designing software systems for distributed information processing networks. Problems as complexity and specific instruments for modeling and control are also presented in a group of papers which identifies a large opening towards the new generation of CPS. The book is structured so as to ensure a good equilibrium between conceptual and applicative aspects.